Fall Prevention - Martie Gillen; Kristen D. Smith; Jenny Jump (EDIS)
Among older adults (those 65 or older), falls are the leading cause of injury and death. When someone falls, they face long-term disability, lower productivity, and loss of independence. Falls can happen anywhere, but more than half of all falls happen at home. Many of these falls could be prevented by making simple changes in the home. This revised 3-page fact sheet was written by Martie Gillen, Kristen D. Smith, and Jenny Jump, and published by the UF Department of Family, Youth and Community Sciences, November 2012.